The Long Run Effects of Oil Prices on Economic Growth: The Case of Libya - Aimer, Nagmi Moftah (International Journal of Social and Administrative Sciences, 2019)
The aim of this paper is to study the impact of price shocks on economic growth in Libya using a sample of annual observations from 1990 to 2016. We apply autoregressive distributed lag (ARDL) models for the analysis of long-run relations between variables. Our estimates suggest that oil price increases have a statistically significant and positive effect on the economic growth of Libya. However, that the positive change 1% in the shock of crude oil prices has a positive impact on Libya's GDP by 0.29%. In addition, the error correction (ECM) results showed that 68% of the imbalance from the previous year's shock converges to the long-term equilibrium in the current year. Overall, the results indicate that crude oil prices have had a positive impact on economic growth in the long-term, while trade openness and imports have had a negative impact on economic growth. Finally, to overcome the impact of fluctuations in oil prices, long-term plans should be initiated to diversify the Libyan economy and gradually reduce dependence on the oil.